SPECTROPHOTOMETRIC METHODS FOR DETERMINATION OF SOFOSBUVIR AND DACLATASVIR IN PURE AND DOSAGE FORMS - Z. SAAD, MONIR; AMER, ATEF; ELGENDY, KHALED; ELGENDY, BASEM (International Journal of Applied Pharmaceutics, 2021)
Objective: Two simple, sensitive and accurate spectrophotometric methods have been developed for the determination of sofosbuvir (SOF) and daclatasvir (DAC) in pure forms and pharmaceutical formulations. Methods: The proposed methods are based on the oxidation of SOF and DAC by a known excess of cerium(IV) ammonium nitrate in sulphuric acid medium followed by determination of unreacted cerium(IV) by adding a fixed amount of indigo carmine (IC) and alizarin red S (ARS) dyes followed by measuring the absorbance at 610 and 360 nm, respectively. The experimental conditions affecting the reaction were studied and optimized. Results: The beer’s law was obeyed in the concentration ranges of 0.2-3.0, 0.2-4.0 for SOF and 0.5-4.5 and 0.5-5.0 μg/ml for DAC using IC and ARS methods, respectively with a correlation coefficient ≥ 0.9991. The calculated molar absorptivity values are 2.354 × 104, 1.933 × 104 for SOF and 1.786 × 104 and 2.015 × 104 L/mol. cm for DAC using IC and ARS methods, respectively u. The limits of detection and quantification are also reported. Intra-day and inter-day precision and accuracy of the methods have been evaluated. Conclusion: The methods were successfully applied to the assay of SOF and DAC in tablets and the results were statistically compared with those of the reference method by applying Student’s t-test and F-test. No interference was observed from the common tablet excipients. The accuracy and reliability of the methods were further ascertained by performing recovery studies using the standard addition method.